2006
DOI: 10.1007/s10554-006-9150-3
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular magnetic resonance in a pregnant patient with absent pulmonary valve syndrome

Abstract: We present a 22 year old Moroccan woman with chronic severe pulmonary regurgitation, who becomes symptomatic in her fourth month of pregnancy. Cardiovascular magnetic resonance, during pregnancy, revealed a large pulmonary aneurysm and turbulent blood flow in the pulmonary trunk with severe pulmonary regurgitation. After gestation, the branch pulmonary arteries were assessed with magnetic resonance angiography and the severely dilated pulmonary arterial trunk and valve were replaced by a pulmonary homograft. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…In the axial plane, we found that the carina and the right and left main bronchi in most cases were just inferior and posterior to the dilated right pulmonary artery and usually both the right and left bronchi were compressed to an equal degree by the dilated right pulmonary artery. Bilateral segmental atelectasis and obstructive emphysema were clearly visualized [10, 11]. Our data demonstrated that most cases (65%) had moderate to severe bronchial stenosis.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…In the axial plane, we found that the carina and the right and left main bronchi in most cases were just inferior and posterior to the dilated right pulmonary artery and usually both the right and left bronchi were compressed to an equal degree by the dilated right pulmonary artery. Bilateral segmental atelectasis and obstructive emphysema were clearly visualized [10, 11]. Our data demonstrated that most cases (65%) had moderate to severe bronchial stenosis.…”
Section: Discussionmentioning
confidence: 66%
“…MRI can demonstrate tracheobronchial compression but it is time-consuming, and prolonged sedation might not be suitable for infants with severe respiratory illness unless performed under general anesthesia [10, 11]. …”
Section: Discussionmentioning
confidence: 99%
“…Published literature reports the use of CMR to delineate specific cardiovascular conditions suspected in pregnancy, including: aortic coarctation, 9 aortic dissection, 10 peri-partum cardiomyopathy, 11,12 and maternal congenital heart disease. 13 Outside of improved visualization, CMR allows for tissue characterization that is not possible using echocardiography. CMR has been used in pregnancy to evaluate and diagnose intra-cardiac masses, 14 acute myocardial infarction, 15 cardiac blood cysts, 16 in addition to evaluation of the myocardium for iron overload (Figure 2).…”
Section: Cmr Applications In Pregnancymentioning
confidence: 99%
“…However, the effect of a gadolinium‐based contrast agent on the fetus is not well‐characterized, and thus should be used only after completion of the first trimester 11 . Magnetic resonance imaging can be used in pregnancy to assess right ventricular dysfunction or pulmonary insufficiency if quantification of these lesions would assist management 12 …”
Section: Cardiac Evaluationmentioning
confidence: 99%
“…11 Magnetic resonance imaging can be used in pre-gnancy to assess right ventricular dysfunction or pulmonary insufficiency if quantification of these lesions would assist management. 12…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%